Comparison of Four Dental Pulp-Capping Agents by Cone-Beam Computed Tomography and Histological Techniques—A Split-Mouth Design Ex Vivo Study - Jayanandan Muruganandhan; Govindarajan Sujatha; Saravanan Poorni; Manali Ramakrishnan Srinivasan; Nezar Boreak; Ahmed Al-Kahtani; Mohammed Mashyakhy; Hitesh Chohan; Shilpa Bhandi; A. Thirumal Raj; Alessio Zanza; Luca Testarelli; et al. (Applied Sciences, 2021)
Dental pulp-capping is done to preserve vital teeth when the pulp is exposed due to caries, trauma or instrumentation. Various materials are used as pulp-capping agents. The introduction of newer materials requires scientific studies to assess their clinical efficacy. The study was designed as a split-mouth randomized analysis of four pulp-capping agents (calcium hydroxide, mineral trioxide aggregate (MTA), Biodentine and EndoSequence root repair material (ERRM)). Based on selection criteria, 15 orthodontic patients requiring the extraction of four premolars (60 teeth total) were included in the study. After pulp-capping, the teeth were extracted after 8 weeks. We analyzed the extracted teeth using cone-beam computed tomography (CBCT) and histological sections to determine the quality of the dentinal bridge and the pulpal response. Ordinal scores were given based on the completeness of the dentinal bridge, the type of bridge and the degree of pulpal inflammation. Results were analyzed using a Kruskal–Wallis test (p < 0.05) with post hoc Conover values being used when applicable. All four pulp-capping materials elicited dentinal bridge formation (60/60). MTA had the highest scores (10/15) in dentinal bridge formation followed by ERRM (8/15). Both materials showed more samples with complete dentinal bridges (9/15 each) and a favorable pulpal response (15/15). Teeth capped with calcium hydroxide showed more cases of incomplete bridge formation (9/15) and pulpal inflammation. These differences in dentinal bridge formation and pulpal inflammation were statistically significant (p 0.001 and p 0.00005, respectively), with post hoc tests revealing no significant differences between MTA and ERRM (p 0.49 and p 0.71, respectively). MTA and ERRM performed better than the other pulp-capping materials but did not differ significantly from each other. The individual preference for a pulp-capping material may be based on clinical efficacy and handling characteristics.